Cardiac function and autonomic cardiac function during a multi-stage cycling event: a brief report - Menard, V.; Barrero, A.; Lachard, T.; Robinault, L.; Li, L.; Schnell, F.; Carré, F.; Le Douairon Lahaye, S. (Frontiers in Sports and Active Living, 2024)
Introduction: Prolonged and repeated exercise performed during an ultra-endurance event can induce general and cardiac fatigue known as exercise-induced cardiac fatigue. Our objective was to find a possible correlation between the cardiac function and the autonomic cardiac function.